NEUTRONIC ANALYSIS OF THE CANDIDATE MULTI-LAYER CLADDING MATERIALS WITH ENHANCED ACCIDENT TOLERANCE FOR WWER REACTORS - Ondřej Novák; Martin Ševeček (Acta Polytechnica CTU Proceedings, 2018)
The paper summarizes preliminary results of neutronic analysis of candidate ATF cladding materials that are under development at the CTU in Prague. To evaluate basic neutronics-related characteristics the Serpent code was used which is a Monte-Carlo based simulation tool. A model of WWER fuel was developed and basic neutronic analysis performed. All coating materials entail certain reactivity penalty compared to reference uncoated cladding that was quantified. The coating of cladding affects also other neutron-physical parameters of cores that modify the performance of the WWER reactors that are discussed.